Aflatoxins: A food safety hazard in Kenyan dairy chains – prevalence, risks and assessment of a biocontrol solution - Ahlberg, S. (University of Helsinki, 2020)
Aflatoxins continue to be a food safety problem globally, especially in developing regions. Prevalent food contaminating aflatoxins are B1 (AFB1) and M1 (AFM1). These are human carcinogens and have potentially severe health impacts. Almost all (99.5 %) milk samples from Nairobi were contaminated with AFM1, highlighting the urgent need to create functional solutions to improve food safety. Based on the aflatoxin levels and milk consumption, risks were calculated: cancer risk caused by AFM1 was lower among consumers purchasing from formal markets (0.003 cases per 100,000) than for low-income consumers (0.006 cases per 100,000) purchasing from informal markets. Overall cancer risk (0.004 cases per 100,000) from AFM1 alone was low. Because of AFM1 in milk, 2.1 % of children below three years in middle-income families, and 2.4 % in low-income families, could be stunted. Overall, 2.7 % of children could hypothetically be stunted due to AFM1 exposure from milk. Based on these results AFM1 levels found in milk could contribute to an average of -0.340 height for age z-score reduction in growth. The exposure to AFM1 from milk is 46 ng/day on average, but children bear higher exposure of 3.5 ng/kg bodyweight (bw)/day compared with adults, at 0.8 ng/kg bw/day.